Effects of postural and kinesthetic awareness on static standing balance and plantar pressure in chronic stroke: a randomized controlled trial - Rauf, Wardah; Sarmad, Samia; Liaqat, Sameed; Saleem, Safa; Jawad, Muhammad; Ahad, Muhammad (Journal of the Pakistan Medical Association, 2024)
Objective: To determine effects of postural and kinesthetic awareness on plantar pressure and static standing stability in chronic stroke patients. Method: The cross-sectional single-blind study was conducted at the University of Lahore Teaching Hospital, Lahore, Pakistan, from January 19 to March 2, 2023, and comprised stroke patients of both genders. aged 45-60 years having visual spatial neglect. They were randomised into control group A and experimental group B. Group A received routine physical therapy, while group B additionally received postural and kinesthetic awareness sessions. Static component of the Berg balance scale was used to measure balance, and PoData Stabiliometeric plate ("Chinesport, Italy") to measure plantar pressure. Data was analysed using SPSS version 25. Results: Of the 52 patients, 26(50%) were in group A with mean age 51.97±4.37 years and mean weight 79.48±5.7kg. The remaining 26(50%) patients were in group B with mean age 50.69±4.41 years and mean weight 78.27±4.55kg. The outcome measures were significantly better in group B compared to group A (p<0.05). Conclusion: Postural and kinesthetic awareness could possibly be a well-grounded rehabilitative strategy that may support and enhance the balance of individuals with chronic stroke. Clinical Trial Number: The study was registered at the United States National Institutes of Health (ClinicalTrials.gov) with registration number NCT05915195 Key Words: Stroke, Postural balance, Proprioception, Kinesthetic sense, Perceptual disorders.